Kontribusi Pengalaman Prakerin dan Kompetensi Kejuruan Terhadap Kesiapan Memasuki Dunia Kerja Industri Siswa Program Teknik Komputer dan Jaringan kelas XII di SMK N 2 Padang Panjang - Mutia Oktavia; Titi Sriwahyuni; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research is purposed to reveal the contribution ofexperience prakerin and vocational competence on industry 'sreadiness to enter the workforce students of computertechniques and network proram class XII in SMK N 2 PadangPanjang. This research is a descriptive correlational . The studypopulation numbered 100 people and sample totaled 50students of class XII computer techniques and networkprogram in SMK N 2 Padang Panjang Academic Year2012/2013 . Technique of random sampling (Simple randomsampling). Data collection using questionnaires anddocumentation. Data were analyzed using Pearson productmoment correlation and multiple correlation for analysis . Theresults of data analysis showed : 1) experience prakerin tocontribute 22.15 % of the student readiness to eter theworkface industry, 2) vocational competence contributed 22.98% to the readiness to eter the workface industry , 3 ) How toexperience prakerin and vocational competence jointlycontributed 34.94 % of industry 's readiness to enter theworkforce students of computer techniques and networkproram class XII in SMK N 2 Padang Panjang. The results ofthis study indicate that the experience prakerin and vocationalcompetence contribute to readiness to enter the workfaceindustry.